Aerobic Vaginitis: is Enterococcus faecalis Another Risk Factor in the Progression of Cervical Intraepithelial Neoplasia to Cervical Cancer—Literature Review - Mahira Jahić; Anis Cerovac (Clinical and Experimental Obstetrics & Gynecology)
Objective: The aim of our review article is to show Enterococcus faecalis (E. faecalis) as a risk factor of cervical cancer. Mechanism: Aerobic vaginitis (AV) is the absence of a balance of vaginal flora containing aerobic and intestinal pathogens, varying degrees of vaginal inflammation and immature epithelial cells. The causes of AV responsible for inflammatory changes are: E. faecalis, Esherichia coli, group B streptococcus and Staphylococcus aureus. The pathogenic effect of aerobic microorganisms such as E. faecalis shows that it causes spontaneous abortion, premature birth, puerperal sepsis, abscesses, and urinary tract infections. Findings in Brief: AV caused by E. faecalis is more common in low-grade and high-grade cervical intraepithelial neoplasia (CIN) than in women with a normal Pap test and is thought to contribute to the progression of cervical cancer. E. faecalis produces hydrogen superoxide which causes chromosomal instability in intestinal epithelial cell infection, which is considered a key factor in the carcinogenic process. The presence of the Human papilloma virus (HPV) 16 gene and genome in E. faecalis in cervical cancer biopsy material leads to a specific link that may be a risk factor in the progression of CIN toward cancer. The presence of HPV in this bacteria can lead to persistent HPV infection, CIN development and progression to cervical cancer. Conclusions: Increased vaginal pH, lactobacilli deficiency, and the ability of E. faecalis to contain HPV-16 in episomal form in E. faecalis-induced AV could be key promoters of persistence and proliferation of cervical HPV as a risk factor in development of CIN and cervical cancer.